A 58-Year-Old Female with Progressive Cough and Right Shoulder Pain - Sanket R. Thakore; Faisal A. Khasawneh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Cavitary pneumonia in immunocompromised patients is a challenging entity. Establishing accurate diagnosis and starting effective antibiotics are essential steps towards improving outcome. A 58-year-old stem cell transplant patient was admitted to the hospital with necrotizing pneumonia caused by nocardia. The disease progressed despite of aggrieve antimicrobial therapy. Nocardiosis continues to be a difficult disease to diagnose and treat.